2003
DOI: 10.1088/0957-4484/15/1/024
|View full text |Cite
|
Sign up to set email alerts
|

In situassembled homojunctions in solution grown PbxFexS nanoparticle films

Abstract: Vacancy induced p–n homojunctions have been successfully grown in situ from an aqueous solution bath in Pb1−xFexS (x = 0.25 and 0.50) semiconductor nanoparticle films. An abrupt change of DC bias to the substrate during growth has been used as a technique to fabricate p–n junctions. (I–V) and (C–V) measurements confirm the formation of homojunctions in the nanoparticle thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Compared with earlier research on the production of DNA nanotubes, our method described here is substantially simpler to grow similar types of DNA nanostructures. We have previously reported that DC bias can be used for changing the majority carrier type in semiconductors [17][18][19]. This was achieved by using a capacitor circuit to manipulate the positive and negative charged species ions in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with earlier research on the production of DNA nanotubes, our method described here is substantially simpler to grow similar types of DNA nanostructures. We have previously reported that DC bias can be used for changing the majority carrier type in semiconductors [17][18][19]. This was achieved by using a capacitor circuit to manipulate the positive and negative charged species ions in the solution.…”
Section: Introductionmentioning
confidence: 99%